STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN - Masdar Mas’ud (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2008)
The study attempts to analyze the factors of capital structure determiner and its impact on company value. The research aims at examining and analyzing the effect of profitability, size, growth opportunity, asset structure, cost of financial distress, and tax shields effects as the capital structure determiners on the manufacturing companies registered at Indonesia Stock Exchange. The differences between the factors of capital structure determiners (consisting of profitability, size, growth opportunity, asset structure, cost of financial distress, and tax shields effects) and the value of manufacturing companie registered at Indonesia Stock Exchange. The sample includes 59 companies registered at Indonesia Stock Exchange the data analysis instrument employed was Structural Equation Modeling (SEM) and t-test. The results of the research indicate that the factors of capital structure determiners, which have significant effect on capital structures, are profitability, size, growth opportunity, asset structure and cost of financial distress. The exception may be tax shields effects, which do not give significant effect at all on capital structure. The latter becomes evident because the depreciation and amortization rates of the registered Indonesia manufacturing company do not seem significant to contribute to company cash flow so that it stands out of company debt proportion.The factors of capital structure determiners with significant effect on capital structures involve profitability, size, asset structure, and cost of financial distress and tax shields effects. Size and growth opportunity do not have significant effect on the capital structure because manufacturing companies consider financing their investment using equity financing to deal with little financial risk regardless the size of company. It shows that there is a similarity on these factors of capital structure determiner between manufacturing company registered at Indonesia Stock Exchange the insignificantly defferent determiner factors pertain to growth opportunity, asset structure and company value. Meanwhile, the difference also develops between the factors of capital structure determiner in the manufacturing company registered at Indonesia Stock Exchange. The significantly different determiner factors will be profitability, size, cost of financial distress; tax shields effects and capital structure.